Microbial biomass and N mineralization in mixed plantations of broadleaves and nitrogen-fixing species - Pereira, E. L.; Santos, S.A.P; Arrobas, M.; Patricio, M.S. (Forest Systems, 2011)
Mixed stands with nitrogen fixing secondary species can improve the vigour and the stand environment of the targeted species. The aim of this study was to better understand the effect of the consociation of a N-fixing species (black locust) with a broadleaf quality timber production (wild cherry). The study was conducted in 11 year old plantations located in the Northeast of Portugal. The treatments considered were: pure black locust, pure wild cherry and mixture of wild cherry and black locust. Each plot had six lines with 12 trees and a buffer strip line. The samplings were collected on the plantation line within a radius of 50 to 100 cm from the tree. In each plot we measured soil N mineralization dynamic, soil microbial biomass carbon (MBC) and nitrogen (MBN), microbial quotient (MBC/Corg), metabolic quotient (qCO2), microbial respiration and dehydrogenase activity. Results showed a positive impact of the black locust species on the supply of nitrogen to the soil. The net N-mineralization rates were, at the end of this study, about three times greater in the pure black locust than in the pure wild cherry and about two times greater in the mixture than in the pure wild cherry. MBC and cumulative soil respiration were higher in the mixture than in the pure cherry plantation soil which may reflect positive changes in the soil environment.